Persepsi Petani terhadap Dukungan Pemerintah dalam Penerapan Sistem Pertanian Berkelanjutan - Ratri Virianita; Tatie Soedewo; Siti Amanah; Anna Fatchiya (Jurnal Ilmu Pertanian Indonesia, 2019)
One of the factors that hinder the adoption of sustainable agriculture technology innovation is the farmers’ perception on the innovation, which is influenced by internal and external factors. One of them is the limited availabilities of infra structure and facilities to support sustainable agricultural production, which are external factors. This research was aimed to analyz the farmers’ perception on the government support in implementing sustainable agriculture system, to find out factors that are related to the farmers’ perception and to produce recommendations that support sustainable agriculture system to the government in the context of sustainable agriculture mainstreaming. This research was conducted in four different areas in Bogor municipality and regency, namely Cimahpar District, Situgede District, Benteng Village, and Purwasari Village. Survey method was used on 201 farmers selected purposively. The results showed that farmers’ perception was negative on government support in implementing sustainable agriculture system. Most of the farmers considered that government provided less support to the implementation of sustainable agriculture system (55.7%). Especially, in providing enough capital (65.7%), insurance on farmers’ business market (58.7%), insurance on the price of business production facilities (51.7%), and insurance on the market (sold with reasonable price) (50.2%). However, factors that were related to the farmers’ perception were formal education (rs = 0.150, P<0.05) and land area (rs = -0.154, P<0.05). Therefore, it is important for the government to provide the farmers’ needs, such as suficient capital, guarantee on market price of farm product, price guarantee for farming production facilities, and market continuity to support sustainable business activities for the continuity of the farmers’ business activity application.